2014
DOI: 10.1371/journal.pone.0109590
|View full text |Cite
|
Sign up to set email alerts
|

The Red Imported Fire Ant (Solenopsis invicta Buren) Kept Y not F: Predicted sNPY Endogenous Ligands Deorphanize the Short NPF (sNPF) Receptor

Abstract: Neuropeptides and their receptors play vital roles in controlling the physiology and behavior of animals. Short neuropeptide F (sNPF) signaling regulates several physiological processes in insects such as feeding, locomotion, circadian rhythm and reproduction, among others. Previously, the red imported fire ant (Solenopsis invicta) sNPF receptor (S. invicta sNPFR), a G protein-coupled receptor, was immunolocalized in queen and worker brain and queen ovaries. Differential distribution patterns of S. invicta sNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…To date, several insect sNPF receptors have been cloned and characterized ( 33 , 41 , 59 68 ). Among these receptors, the sNPFRs from D. melanogaster ( 67 , 68 ), A. gambiae ( 60 ), B. mori ( 41 , 61 ), S. gregaria ( 33 ), A. aegypti ( 62 ), S. invicta ( 63 ), G. m. morsitans ( 64 ), and the oriental fruit fly, Bactrocera dorsalis (Hendel) ( 65 ) have been deorphanized by ligand-receptor activation of signaling in a heterologous cell expression system, with EC 50 values in the nanomolar range. Compared to the high sensitivity of insect sNPFRs, Sp -sNPFR in our study had a relatively higher half-maximal effective concentration (EC 50 ) in the HEK293T expression system.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several insect sNPF receptors have been cloned and characterized ( 33 , 41 , 59 68 ). Among these receptors, the sNPFRs from D. melanogaster ( 67 , 68 ), A. gambiae ( 60 ), B. mori ( 41 , 61 ), S. gregaria ( 33 ), A. aegypti ( 62 ), S. invicta ( 63 ), G. m. morsitans ( 64 ), and the oriental fruit fly, Bactrocera dorsalis (Hendel) ( 65 ) have been deorphanized by ligand-receptor activation of signaling in a heterologous cell expression system, with EC 50 values in the nanomolar range. Compared to the high sensitivity of insect sNPFRs, Sp -sNPFR in our study had a relatively higher half-maximal effective concentration (EC 50 ) in the HEK293T expression system.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some of our pioneering work focused on a G‐protein‐coupled receptor (GPCR) signaling system, the sNPF (sNPY) system. We showed that mated queen starvation resulted in the significant reduction in sNPF receptor transcripts in queen brains suggesting this system links nutrition and reproduction (Ament, Velarde, Kolodkin, Moyse, & Robinson, ; Bajracharya, Lu, & Pietrantonio, ; Chen & Pietrantonio, ). Importantly, the sNPF receptor protein is present in the brain of both virgin and mated queens but it is only expressed in oocytes in ovaries of mated queens (Lu & Pietrantonio, ).…”
Section: Introductionmentioning
confidence: 95%
“…1, center, Processes). Functional analyses of arthropod receptors utilizes calcium mobilization assays (using bioluminescence [27] or fluorescence), or by measurements of cAMP [28]. These are G-protein dependent assays often used in academic settings for forward pharmacology and can be low-throughput or high-throughput (Fig.…”
Section: Omics Aids Gpcr Discovery Functional Characterization and Dmentioning
confidence: 99%
“…It was not until the release of the fire ant genome and confirmation by cloning a cDNA encoding an unusual sNPYa that we succeeded: Two potential ligands predicted from the translated sequence activated the recombinant receptor by decreasing cAMP in CHO-K1 cells. Mass spectrometry of queen brain confirmed the presence of one peptide fragment [28].…”
Section: Omics Aids Gpcr Discovery Functional Characterization and Dmentioning
confidence: 99%